1974
DOI: 10.1088/0022-3727/7/15/317
|View full text |Cite
|
Sign up to set email alerts
|

M$ouml$ssbauer study of Egyptian goethite

Abstract: Mossbauer spectroscopy has been used for the study of Egyptian goethite from different deposits of the Bahariya Oasis, in order to identify the different iron forms in the ore, and to investigate the physical properties of the mineral and its changes according to the geochemical conditions under which the ore was formed. Four representative samples were selected: the first one showed the existence of haematite with goethite, which is the normal final form to which goethite is transformed under high temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The analogous data for magnetite-based mixed coated MFs bearing the same surfactants and possessing the highest (7) and the lowest cytotoxicities (8) It was found that the water-based solution of goethite nanoparticles 5 exhibits cytotoxicity against human fibrosarcoma HT-1080 and mouse hepatoma MG-22A, which approximates to the less active magnetite-based sample, and possesses moderate NO induction ability. The magnetic fluid therapeutic index (TI MF ) of 5, which is calculated as the ratio of LC 50 determined for normal cells to LC 50 for tumor cells, [4] ranges from 1.6 to 2.4 depending on the kind of tumor and the test.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…The analogous data for magnetite-based mixed coated MFs bearing the same surfactants and possessing the highest (7) and the lowest cytotoxicities (8) It was found that the water-based solution of goethite nanoparticles 5 exhibits cytotoxicity against human fibrosarcoma HT-1080 and mouse hepatoma MG-22A, which approximates to the less active magnetite-based sample, and possesses moderate NO induction ability. The magnetic fluid therapeutic index (TI MF ) of 5, which is calculated as the ratio of LC 50 determined for normal cells to LC 50 for tumor cells, [4] ranges from 1.6 to 2.4 depending on the kind of tumor and the test.…”
Section: Resultsmentioning
confidence: 76%
“…[6] Mineral goethite is weakly magnetic and belongs to the group of antiferromagnetic materials which need high magnetic field in order to reach magnetic saturation. [7,8] Negligible isothermal remanence up to 4 T in synthetic goethites was reported. [9] The data adduced in the literature for Neel point at which synthetic goethite transforms from the antiferromagnetic state to the paramagnetic state are different: 392 K, which is in agreement with the natural samples, [8] and 252 K for goethite nanoparticles, which is significantly lower than the corresponding bulk values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2b; Table 1), the spectrum was fitted with two six-line patterns with different hyperfine magnetic field values. The value of 462 kOe (δ/Fe = 0.49 mm/s) is probably from goethite (Eissa et al 1974;Murad 1989;Bocquet et al 1992). The smaller value of 431 kOe (δ/Fe = 0.48 mm/s) could originate from one of two possible causes: an impure goethite (with an impurity such as Al) or an effect arising from small particle sizes (van der Kraan and van Loef 1966;Golden et al 1979;Mørup et al 1982;Bocquet et al 1992).…”
Section: Mineralogical and Geochemical Characterisation Of Ard Sedimentmentioning
confidence: 96%